Active monitoring of a hydraulic fracture propagation: Experimental and numerical study - Nabipour, Amin; Evans, Brian; Sarmadivaleh, Mohammad (Australian Petroleum Production and Exploration Association Limited, 2011)
Hydraulic fracturing is known as one of the most common stimulation techniques performed on oil and gas wells for maximising hydrocarbon production. It is a complex procedure due to numerous influencing factors associated with it. As a result, hydraulic fracturing monitoring techniques are used to determine the real-time extent of the induced fracture and to prevent unwanted events. Although the well-known method of monitoring is the microseismic method, active monitoring of a hydraulic fracture has shown capable of providing useful information about the fracture properties in both laboratory conditions and field operations. In this study, the focus is on laboratory experiment of hydraulic fracturing using a true-triaxial stress cell capable of simulating field conditions required for hydraulic fracturing. By injecting high-pressure fluid, a hydraulic fracture was induced inside a 20 cm cube of cement. Using a pair of ultrasonic transducers, transmission data were recorded before and during the test. Both cases of an open and closed hydraulic fracture were investigated. Then, using a discrete element scheme, seismic monitoring of the hydraulic fracture was numerically modelled for a hexagonally packed assembly and compared with the lab results.The results show good agreements with data in the literature. As the hydraulic fracture crosses the transducers line, signal dispersion was observed in the compressional wave data. A decrease was observed in both the amplitude and velocity of the waves. This can be used as an indicator of the hydraulic fracture width. As the fracture closes by reducing fluid pressure, a sensible increase occurred in the amplitude of the transmitted waves while the travel time showed no detectable variations. The numerical model produced similar results. As the modelled hydraulic fracture reached the source-receiver line, both amplitude and velocity of the transmitted waves decreased. This provides hope for the future real-time ability to monitor the growth of induced fractures during the fraccing operation. At present, however, it still needs improvements to be calibrated with experimental results.